103k views
5 votes
What is the answer to this question?

What is the answer to this question?-example-1

2 Answers

6 votes

Answer: The Answer is A X=0 Y=2/3

Explanation:

2x+3y=2

X+6y=4

step one: substitute in the value of x into the equation

2x +3y = 2

x= 4-6y

Step two: Solve with the X substitution

2(4-6y) +3y = 2

You get Y= 2/3

Step three: plug in 2/3 for X

X= 4-6(2/3)

You get 0

therefore: X = 0 and Y=2/3

User Kurt McKee
by
4.9k points
3 votes

Answer:

(0,2/3)

Explanation:

I would go for elimination on this one.

This will require we manipulate at least one equation.

I'm going to multiply bottom equation by -2: -2x-12y=-8

So we have

2x+3y=2

-2x-12y=-8

---------------add the two equations

0 -9y=-6

-9y=-6

y=6/9=2/3

2x+3y=2

2x+3(2/3)=2

2x+2=2

2x=0

x=0

(0,2/3)

User Vlad Stratulat
by
5.5k points